Going Concern Different Variables of Indonesia Manufacturing Companies - Yulianto, Tuk; Ratnawati, Tri; Pristiana, Ulfi (KnE Social Sciences, 2023)
This was a quantitative descriptive study with a sample of 25 manufacturing companies on the Indonesia Stock Exchange, for 4 consecutive years so the number of units of analysis is 100 with the time series cross-sectional method (pulling data). The analysis technique used was discriminant statistics that were processed with SPSS. The distinguishing variables were investment decisions, size, risk management, profitability and cash flow. The profitability variable had a value of Wilks ’Lambda of 0.013 and a significance of 0.000 which meant that the profitability variables tend to have differences in groups because they have a value of Wilks’ Lambda approaching 0 and hypothesis decisions had differences in groups because Significance is below 0.05, causing the hypothesis to be rejected. Keywords: kwd